Growth of silicon viskers by vapor-liquid-crystal method - Gorbyk, P. P.; Dubrovin, I. V.; Demchenko, Yu. A.; Filonenko, M. N.; Dadykin, A. A. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2007)
A method of fabrication of regular areas with randomly distributed gold nanoparticles on polished silicon surfaces has been developed. The processes of silicon whiskers formation by the "vapor-liquid-crystal" technique have been investigated. The structure, morphology and emission properties of whiskers have been studied.